'It was like coming back from the clouds': a qualitative analysis of the lived experience of overdose consequent to drug use among a cohort of people who use drugs in Scotland - Christopher J. Byrne; Fabio Sani; Teresa Flynn; Amy Malaguti (BMC, 2024)
Abstract Background Globally, non-fatal overdose (NFOD) rates consequent to drug use, typically opioids, continue increasing at a startling rate. Existing quantitative research has revealed myriad factors and characteristics linked to experiencing NFOD, but it is critically important to explore the lived context underlying these associations. In this qualitative study, we sought to understand the experiences of NFOD among people who use drugs in a Scottish region in order to: enhance public policy responses; inform potential intervention development to mitigate risk; and contribute to the literature documenting the lived experience of NFOD. Methods From June to July 2021, two peer researchers conducted face-to-face semi-structured interviews with people who use drugs who had experienced recent NFOD attending harm reduction services in Tayside, Scotland. These were transcribed verbatim and evaluated using thematic analysis with an inductive approach which had an experiential and essentialist orientation. Results Twenty people were interviewed across two sites. Of those, 15 (75%) were male and mean age was 38.2 (7.7) years. All had experienced at least one NFOD in the prior six months, and all reported polydrug use. Five themes were identified, within which 12 subthemes were situated. The themes were: social context; personal risk-taking triggers; planned and impulsive consumption; risk perception; and overdose reversal. The results spoke to the environmental, behavioural, cognitive, economic, and marketplace, factors which influence the context of NFOD in the region. Conclusions A complex interplay of behavioural, psychological, and situational factors were found to impact the likelihood of experiencing NFOD. Structural inequities which policy professionals and civic leaders should seek to remedy were identified, while service providers may seek to reconfigure healthcare provision for people who use drugs to account for the interpersonal, psychological, and social factors identified, which appear to precipitate NFOD. Trial registration Not applicable.